2019
DOI: 10.3892/ijmm.2019.4324
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine induces autophagy in biliary cancer cells via�reactive oxygen species-activated Erk signaling pathway

Abstract: Biliary cancer (BC) is an aggressive neoplasm with high mortality. BC can be categorized into three groups: Intrahepatic cholangiocarcinoma (CCA; also known as bile duct cancer), extrahepatic cholangiocarcinoma and gallbladder cancer. Due to its heterogeneity and aggressiveness, the response to current chemotherapy and radiotherapy methods in patients with BC is poor. Therefore, there is an urgent requirement to develop drugs to treat BC. Piperlongumine (PL), a naturally occurring small molecule isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
1
20
0
1
Order By: Relevance
“…Four natural compounds have been recently described to induce CCA cell death, implicating the activation of autophagy as a mediator of their cytotoxic effects:piperlongumine (small molecule extracted from Piper longum plant [151]), pterostilbene (an active constituent of blueberries [152]), pristimerin (a triperpenoid isolated from Maytenus heterophylla [153]) and dihydroartemisinin (an active compound found in Artemisia annua [154]). Although it has been proven that autophagy induction is necessary for their mechanism of action, the specific molecular mechanisms governing their autophagy modulation abilities are not fully understood yet.…”
Section: Autophagy Activatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four natural compounds have been recently described to induce CCA cell death, implicating the activation of autophagy as a mediator of their cytotoxic effects:piperlongumine (small molecule extracted from Piper longum plant [151]), pterostilbene (an active constituent of blueberries [152]), pristimerin (a triperpenoid isolated from Maytenus heterophylla [153]) and dihydroartemisinin (an active compound found in Artemisia annua [154]). Although it has been proven that autophagy induction is necessary for their mechanism of action, the specific molecular mechanisms governing their autophagy modulation abilities are not fully understood yet.…”
Section: Autophagy Activatorsmentioning
confidence: 99%
“…Although it has been proven that autophagy induction is necessary for their mechanism of action, the specific molecular mechanisms governing their autophagy modulation abilities are not fully understood yet. Piperlongumine induced apoptosis [155] and autophagy [151] in CCA cells through the production of ROS, induction of ER stress and activation of JNK-ERK signaling pathway [151]. Similar to piperlongumine, dihydroartemisinin is an antimalaria drug that induces ROS-mediated ER stress through DAPK activation, promoting the disruption of Beclin1-Bcl-2 complex and inducing autophagy-mediated CCA cell death, therefore activating initiation of autophagy.…”
Section: Autophagy Activatorsmentioning
confidence: 99%
“…Previous reports have shown that various plant extracts can induce both apoptosis and autophagy in CCA cells [24,39]. According to our current results, BJA could induce apoptosis in KKU-213 cells; therefore, the other mode of action via autophagy was investigated.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have shown that autophagy is considered as another response mechanism of CCA to several chemotherapy treatments [ 24 , 25 , 26 ]. Hence, in order to determine the effect of BJA-95 on the autophagy induction in CCA, autophagic vacuoles were imaged by fluorescence microscopy ( Figure 4 A) and were then quantitated by flow cytometry ( Figure 4 B).…”
Section: Resultsmentioning
confidence: 99%
“…Induction of ROS by piperlongumine purportedly occurs by activation of the Erk signaling pathway, and has been shown to induce cell cycle arrest in cholangiocarcinoma cells (HuCCT-1) and gallbladder cancer cells (OCUG 1). Piperlongumine also caused G2/M cell cycle arrest in HuCCT 1 cells and G0/ G1 cell cycle arrest in OCUG 1 cells [29]. Still another study showed an increase in the sensitivity of colorectal cancer cells in association with changes to ROS homeostasis due to inhibition of glutathione production and thioredoxin function by treatment with piperlongumine [30].…”
Section: Anticancer Amides From Piper Plantsmentioning
confidence: 94%